2013
DOI: 10.1155/2013/658596
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Flavonoids, Phenolic Acids, and Xanthines inMateTea (Ilex paraguariensisSt.-Hil.)

Abstract: Raw material, different formulations of foods, and dietary supplements of mate demands control of the content of bioactive substances for which high performance thin layer chromatography (TLC), described here, presents simple and rapid approach for detections as well as quantification. Using TLC densitometry, the following bioactive compounds were identified and quantified: chlorogenic acid (2.1 mg/g), caffeic acid (1.5 mg/g), rutin (5.2 mg/g), quercetin (2.2 mg/g), and kaempferol (4.5 mg/g). The results obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Mean values by the same letter within a row do not differ significantly according to Tukey's post hoc test at α <0.05 reported in the literature concerning studies of phenolics in erva-mate (Bojic et al 2013) and herbal teas (da Silva Port's et al 2013). Veljković et al (2013) determined individual phenols in black and green tea infusions and found that green teas are richer in phenolic compounds than black teas.…”
Section: Phenolic Compounds and Alkaloidsmentioning
confidence: 82%
See 1 more Smart Citation
“…Mean values by the same letter within a row do not differ significantly according to Tukey's post hoc test at α <0.05 reported in the literature concerning studies of phenolics in erva-mate (Bojic et al 2013) and herbal teas (da Silva Port's et al 2013). Veljković et al (2013) determined individual phenols in black and green tea infusions and found that green teas are richer in phenolic compounds than black teas.…”
Section: Phenolic Compounds and Alkaloidsmentioning
confidence: 82%
“…After Paraguay, Brazil is the second producer of erva-mate in the world (Neto et al 2007). Methylxanthines, represented by caffeine, are among the compounds present in erva-mate (Bojic et al 2013). Moreover, infusions prepared from erva-mate can influence human well-being; for instance, they can stimulate antirheumatic and anti-inflammatory and diuretic activities (Jacques et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…15,23 Therefore, we designed a clinical study to investigate the effects of Maté, whose weight and body fat loss effects have been verified in previous studies, on human subjects. Adults, who were obese but otherwise healthy, were made to ingest 3,000 mg of Maté extract over a 6-week period, and reductions in their body weight and WC were compared to the control group to assess the effectiveness of Maté.…”
Section: Discussionmentioning
confidence: 99%
“…Yerba-mate extracts show a high level of phenolic acids and flavonoids. Rutin, followed by kaempferol, is the most abundant flavonoid in yerba-mate (Bojić, Simon Haas, Šarić, & Maleš, 2013). The role of these metabolites in health has been extensively studied during the last years.…”
Section: Discussionmentioning
confidence: 99%